Trabajo de suficiencia profesional como asistente administrativo en la empresa Garna Industrial S.A.C. Período 2015-2018 - García Namuche, Carlos Ramiro (2018)
The present work of his professional proficiency as an administrative assistant was carried out in the company Garna Industrial S.A.C; dedicated to the manufacture and services of machining parts for the metal-mechanic industrial sector. Being a young company, the demand for the service is variable and subject to various factors. In an initial diagnosis, he said that he had problems with liquidity, skilled labor and problems in the delivery of mechanized parts at the agreed times. One of the weaknesses of this company is directed by people with limited managerial knowledge; Even with this limitation, investors survive that new competitors are entering, which means that the business has to adopt new management and development strategies, based on customer satisfaction and thus face the strong competition of the sector. This report aims to analyze the quality of service and customer satisfaction, in order to position the brand, retain their customers and attract potential customers; as well as the good management of the company. Making an analysis of my work performed, the functions such as: technical visits to the different companies in the sector, quoting in the port B2MINIG, supervision, invoice management efficiently. Finally the work carried out and the proposed proposals were analyzed, the partners determined that they are economically feasible and of contribution for the company, which leads me to satisfaction for the function performed.